Generation of a variable bias voltage for inductorless-LNA process effect compensation - Martínez Pérez, Antonio D; Paredes Páliz, Diego F.; Aznar, Francisco; Celma, Santiago (Jornada de Jóvenes Investigadores del I3A, 2022)
This work presents and evaluates different alternatives to implement a bias circuit that compensates for variations in the manufacturing process in a low noise amplifier (LNA) based on a common gate stage with transconductance enhancement. The study covers three topologies and a comparison and verification is made through corner analysis and Monte Carlo.